Perancangan Service Dominant Logic Pada UMKM Pariwisata Kawasan Danau Toba Dengan Pendekatan Business Model Canvas : Indonesia - Simanungkalit, Ambar; Simanjuntak, Mariana (Asian Journal of Innovation and Entrepreneurship, 2024)
MSME is a productive business, generally carried out by individuals or cer-tain business entities in the economic sector. In the tourism sector, MSMEs are small to medium sized businesses that focus on providing tourism related products and services. This study aims to identify the extent to which the perspective of the Service-Dominant Logic concept has been applied in tourism MSMEs in the Toba Region, especially Lapo Toba MSMEs, and to determine the effect of Business Model Canvas in implementing service de-sign to improve MSME performance. In this study, customers are considered as actors, so value co-creation variables are used in the services provided by tourism MSME players, so it is necessary to understand the satisfaction and demand from customers for the services provided by tourism MSME players in the Toba Region.